2005
DOI: 10.1086/426617
|View full text |Cite
|
Sign up to set email alerts
|

Information Accessibility as a Moderator of Judgments: The Role of Content versus Retrieval Ease

Abstract: We hypothesize that the accessibility of task-relevant knowledge determines whether judgments reflect the substance of the information that is brought to mind or the ease of generating and retrieving such information. Our findings indicate that when relevant knowledge is highly accessible or not at all accessible, judgments are based on the content of the information considered. Between these extremes in knowledge accessibility, judgments are based on the perceived ease with which information can be retrieved.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 24 publications
(31 reference statements)
8
77
0
2
Order By: Relevance
“…The most widely studied lay theory of memory is at the heart of Tversky and Kahneman's (1973) availability heuristic. It correctly holds that it is easier to recall examples when many rather than few exist in the world; hence people infer frequency and typicality from ease of recall (Schwarz et al, 1991;Tybout, Sternthal, Makaviya, Bakamitsos, & Park, 2005;Wanke, Bohner, & Jurkowitsch, 1997). However, people hold many other, usually correct, lay theories of memory.…”
Section: Metacognitive Inferencesmentioning
confidence: 99%
“…The most widely studied lay theory of memory is at the heart of Tversky and Kahneman's (1973) availability heuristic. It correctly holds that it is easier to recall examples when many rather than few exist in the world; hence people infer frequency and typicality from ease of recall (Schwarz et al, 1991;Tybout, Sternthal, Makaviya, Bakamitsos, & Park, 2005;Wanke, Bohner, & Jurkowitsch, 1997). However, people hold many other, usually correct, lay theories of memory.…”
Section: Metacognitive Inferencesmentioning
confidence: 99%
“…It is also important for future research to examine the conditions under which the experience of ease or diffi culty of imagining the product experience is likely to be perceived as diagnostic (Tybout, Sternthal, Malaviya, Bakamitsos, & Park, 2005;Zhao, Hoeffl er, & Dahl, 2007). For example, consumers may not be infl uenced by the experience of diffi culty imagining the product experience for product categories that are generally diffi cult to imagine.…”
Section: When Does Imagery Infl Uence Consumers' Judgments?mentioning
confidence: 99%
“…Research has for example shown that a failure to recall a specified number of positive evaluations relating to an object decreases the final evaluation (Fazio 1995). For example, if a BMW fanatic is asked to name ten advantages of a BMW over a Mercedes, which is a challenging task, one observes a decrease in the overall evaluation of the BMW (Tybout et al 2005). This decrease is present only when ten advantages are asked for, and is not present when three advantages are asked for.…”
Section: The Formation Of Attitudesmentioning
confidence: 99%